First Report of Meloidogyne enterolobii on Cultivated Fenugreek, Trigonella corniculata L.in India (Indian Journal of Nematology, 2024)
Cultivated fenugreek Trigonella corniculata L, also known as kasuri methi or nagauri paan is a popular spice crop and widelygrown in the state of Rajasthan, India. Galls and root-knot nematodes were observed on the roots of T. corniculata collected from Naguar district and its surrounding areas in the state of Rajasthan. The nematode DNA isolated from the sample was subjected to PCR by using species-specific primers for the common root-knot nematode species. Molecular identification confirmed the infestation of Meloidogyne enterolobii on T. corniculata. This is the first report of M. enterolobii infestation on T. corniculata from India.